"Playing the game", identity and perception-of-the-other in water cooperation in the Jordan River Basin. Issue 7 (18th May 2016) - Wessels, Josepha Ivanka
ABSTRACT: The concept of Integrated Water Resources Management (IWRM) has enjoyed immense popularity and thus has been the preferred approach for river basin management. IWRM generally has a strong focus on rational choice, based on a technocratic conceptual interpretation of the conventional hydrological cycle. However, uncritical acceptance of IWRM runs the risk of blinding policy makers and academics for the defining impact of context, socio-cultural, political, historical and cognitive dimensions in water cooperation. Human behaviour in water cooperation was tested and observed during eight experiments with the Jordan River Basin Boardgame Exercise (JRBBE) played with respondent groups from inside and outside the Jordan River Basin. The experiments consisted of one control group outside the basin and seven respondent groups both outside and inside the basin. This article argues that the role of identities, beliefs and perception-of-the-other, should be taken more into account in order to develop successful and socio-political sustainable river basin management.EDITOR D. Koutsoyiannis;ASSOCIATE EDITOR not assigned